The Evaluatıon Of Patıent Cooperatıon In Turkey - Enis Güray; Metin Orhan; Elif Ertaş (Galenos Yayinevi, 1994)
The patient cooperation plays a major role in the success of orthodontic treatments. Orthodontists often face the patient and/or parent cooperation problem and devote most of their clinical time to find solutions. Over the years, several papers, suggesting methods to predict patient cooperation were published. Such studies claimed that it was adequately possiblerto predict the success of the future orthodontic treatment. The present study was planned to evaluate the characteristics of patients undergoing orthodontic treatment in our society and to investigate the possible variables in predicting patient complience. Questionnaires were sent to 204 (10 for each) orthodontists. They were asked to fill the questionnaires for their patients who were under active treatment for minimum of 6 months. The collected data was analysed and scored according to "Orthodontic Patient Cooperation Scale" (OPCS) as described by Slatker and Albino. The results indicated that age was not significantly correlated with the patient cooperation. However girls between 15-18 years old were slightly more cooperative than the boys. Neither patient/parent education level, social status, treatment fee nor the location of the orthodontic service had significant association with patient complience. The type and the severity of the malocclusion were not significantly correlated with the patient complience while treatment time found to be associated with cooperative treatment.